The Value of Indigenous Saccharomyces cerevisiae Strains as Useful Enzymes Producers: A Systematic Review - Andrade Koelher, Bárbara Teodora; Magalhães, Valter Cruz; Rodrigues dos Santos, Lorena Brito Pimentel; Loguercio, Leandro Lopes; Trovatti Uetanabaro, Ana Paula; Reis Figueirêdo, Antônio Fábio; Flores Santos, Mateus Pereira; Costa, Andréa Miura da (Food Science and Engineering, 2024)
This systematic review has focused on the selection and characterization of indigenous Saccharomyces cerevisiae strains for enzymes' production obtained from the fermentation process. The primary studies assessed have demonstrated that indigenous S. cerevisiae strains produce a wide range of enzymes during fermentation. These strains have shown different characteristics and were isolated from various locations, including those belonging to the main components of the wine production chain. The research methodology applied to find primary studies about the optimal conditions for enzyme production was effective and identified a wide range of enzyme classes. Cultivation media amended with natural or synthetic inducer substrates were found to be suitable carbon and/or nitrogen sources for producing enzymes of interest in plate-based screening. In submerged fermentation studies, the use of agro-industrial residues has been identified as a relevant carbon source for microbe development and metabolism. For the indigenous S. cerevisiae strains, the majority of the enzymes found belong to the glucosidases and hydrolases classes. Due to the activity of these enzymes, yeasts have been traditionally used in classic biotechnological applications, particularly in the process of alcoholic fermentations. Those enzymes are responsible for producing metabolites (such as aromatic compounds) that contribute to the desirable aroma and/or taste during the fermentation of wine, as well as other fermented or distilled beverages. The methods used for enzyme screening were of quantitative and/or qualitative nature and were carried out under acidic pH conditions (3.5-6.5) and at temperatures of 28-35 ℃. The results of this systematic review have shown that the enzymes from indigenous S. cerevisiae are highly relevant in various biotechnological applications, particularly in the food industry. Conclusions and future perspectives of our findings were discussed in terms of potential developments of novel application methods of the indigenous yeasts and their enzymes in agriculture and industry.